High-fiber diet mitigates maternal obesity-induced cognitive and social dysfunction in the offspring via gut-brain axis - Liu, Xiaoning; Li, Xiang; Xia, Bing; Jin, Xin; Zou, Qianhui; Zeng, Zhenhua; Zhao, Weiyang; Yan, Shikai; Li, Ling; Yuan, Shufen; Zhao, Shancen; Dai, Xiaoshuang; et al. (Cell metabolism, 2021)
Maternal obesity has been reported to be related to neurodevelopmental disorders in the offspring. However, the underlying mechanisms and effective interventions remain unclear. This cross-sectional study with 778 children aged 7–14 years in China indicated that maternal obesity is strongly associated with children’s lower cognition and sociality. Moreover, it has been demonstrated that maternal obesity in mice disrupted the behavior and gut microbiome in offspring, both of which were restored by a high-fiber diet in either dams or offspring via alleviating synaptic impairments and microglial maturation defects. Co-housing and feces microbiota transplantation experiments revealed a causal relationship between microbiota and behavioral changes. Moreover, treatment with the microbiota-derived short-chain fatty acids also alleviated the behavioral deficits in the offspring of obese dams. Together, our study indicated that the microbiota-metabolites-brain axis may underlie maternal obesity-induced cognitive and social dysfunctions and that high dietary fiber intake could be a promising intervention. [Display omitted] •Maternal obesity is associated with cognition and sociality decline of children•Maternal or offspring’s high-fiber diet prevents offspring’s behavioral disorders•High-fiber diet alleviates synaptic impairments and microglial maturation defects•Microbiota-SCFA-brain axis mediates maternal obesity-induced behavioral disorders Maternal obesity is related to neurodevelopmental disorders in the offspring. Liu and colleagues demonstrate that maternal obesity is strongly associated with children’s lower cognition and sociality. A high-fiber diet restores maternal obesity-induced behavioral disorders via mediating gut microbiota-SCFA-brain axis and improving synaptic impairments and microglial maturation defects in the offspring.